Chemical Composition And Nanoencapsulation Of Cynometra Cauliflora Essential Oils And Their Biological Activity Studies - Samling, Benedict (2023)
Cynometra cauliflora L., locally known as “nam-nam” or “katak puru” in Malaysia belongs to the Fabaceae family. The tree is cultivated in villages and has been used traditionally to treat appetite loss, skin disorders, diabetic, and cholesterol related problems. Thus far, limited studies have been conducted on C. cauliflora. The present study aimed to identify the essential oils (EOs) composition of the leaf, twig and fruit of C. cauliflora and to encapsulate the EOs in chitosan nanoparticles (CSNPs). Antioxidant, antimicrobial and cytotoxic activities were performed to assess the free and encapsulated EOs. The identification of EOs constituents was made using capillary GC and GC-MS. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity was employed to assess the antioxidant activity.